SOSIALISASI PENGEMBANGAN KAPAL MODERN BERBASIS TEKNOLOGI TERINTEGRASI BERSAMA KELOMPOK NELAYAN DESA JENILU: SOCIALIZATION OF MODERN SHIP DEVELOPMENT BASED ON INTEGRATED TECHNOLOGY TOGETHER WITH THE FISHERMAN GROUP OF JENILU VILLAGE - Adam Tnunay, Imanuel; Hakim, Moh. Lukman; Pereira Maia Pinto, Gaspar; Bilak Lopo, Elkana; Nisen Laosana, Okto Rosario (Blueprint Journal, 2026)
Traditional fishermen in Jenilu Village still face limitations in the utilization of modern marine vessel technology, particularly in terms of ship machinery systems, work safety, and operational efficiency. These conditions contribute to a high risk of maritime accidents and low fishing productivity. This community service activity aims to enhance the understanding of fishermen groups in Jenilu Village regarding the development of modern vessels based on integrated technology. The activity was conducted using a participatory-educational approach, including socialization sessions, interactive discussions, and field observations. The results indicate an improvement in fishermen’s understanding of modern vessels as integrated systems consisting of main engines, supporting systems, and safety equipment. The fishermen also showed positive responses and strong interest in adopting technologies that can improve vessel safety and operational efficiency. This activity is expected to serve as an initial step toward transforming traditional fishing vessels into more modern, safe, and sustainable vessels in coastal areas.